PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL - Bjorn Patrick Ibrahim; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2023)
This research aims to obtain empirical evidence regarding the effect of liquidity, profitability, firm size and asset structure on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This study used 76 samples from manufacturing companies selected by purposive sampling method. The data used are secondary data in the form of financial reports. Data processing in this study using the E-views 10.0 program. The results of this study indicate that liquidity have negative and significant effect on capital structure, profitability have negative and significant effect on capital structure, firm size have positive and significant effect on capital structure, and asset structure have negative and significant effect on capital structure. For future research, it is recommended to adding other independent variables, extending the research period, and increase the company's sector.